Principales factores del bienestar sanitario en México 2000-2020. Un estudio a través de datos de panel - Carrillo Gómez, Daniel (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
Health has evolved during the last 20 years in the member countries of the WHO, they have adapted their conception of health beyond the lack of disease, to conceive it as justice for their citizens. Mexico has not been the exception in adapting this right in its magna carta. Throughout the federal administrations, a series of health policies have been articulated that have increased the national life expectancy. This research set out the objective of identifying the main factors that affected health and well-being in Mexico from the period 2000-2020. To this end, the states and Mexico City (formerly the Federal District) were analyzed using an econometric model of dynamic least squares panel data, studying the sample units (States) and their fluctuations over 21 years. The calculations of the State Health Index were made using the UNDP methodology as an indicator of health well-being. Data from the General Directorate for Health Systems Performance Evaluation were analyzed for the independent variables. The results showed that there is a long-term relationship between the variables: a) surgical interventions per thousand inhabitants, b) the number of family doctors per thousand inhabitants, c) the daily average of medical consultations, d) incidence of infant malnutrition in children under 5 years of age and e) public spending on health as a percentage of total spending. Variables a and b are the most significant, showing the importance of medical personnel in health in Mexico and their surgical facilities in order to achieve health and well-being in Mexico.

La sanidad ha evolucionado durante los últimos 20 años en los países miembros de la OMS, estos han adaptado su concepción de la salubridad más allá de la falta de enfermedad, para concebirla como una justicia para sus ciudadanos. México no ha sido la excepción adaptando este derecho en su carta magna. A lo largo de las administraciones federales se ha articulado una serie de políticas sanitarias que han aumentado la esperanza de vida nacional. Esta investigación se planteó el objetivo de identificar los principales factores que incidieron con el bienestar sanitario en México del periodo 2000-2020. Para este fin, se analizaron a las entidades federativas y Ciudad de México (anteriormente Distrito Federal), por medio de un modelo econométrico de datos de panel de mínimos cuadrados dinámicos, estudiando las unidades muestrales (Estados) y sus fluctuaciones a lo largo de 21 años. Se realizaron los cálculos del Índice de Salud Estatal mediante la metodología del PNUD como indicador del bienestar sanitario. Se analizaron datos de la Dirección General de Evaluación al Desempeño de los Sistemas de Salud para las variables independientes. Los resultados arrojaron que existe una relación al largo plazo de las variables: a) intervenciones quirúrgicas por cada mil habitantes, b) número de médicos familiares por cada mil habitantes, c) promedio diario de consultas médicas, d) Incidencia de desnutrición infantil en niños menores de 5 años y e) gasto público en salud como porcentaje del gasto total. Las variables a y b son las más significativas, mostrando la importancia del personal médico en la salud en México y sus las instalaciones quirúrgicas para poder alcanzar el bienestar sanitario en México.
Instituto de Investigaciones Económicas y Empresariales. Doctorado en Políticas Públicas
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16362; info:eu-repo/classification/cti/5; ININEE-D-2023-0507; Sistemas de salud; Índice de salud estatal; Datos de panel